Google hacking for penetration testers - Long, Johnny (Syngress, 2005)
Annotation
Keywords: Google; Web search engines; Internet searching; Internet programming; Moteurs de recherche sur Internet; Recherche sur Internet; Programmation Internet; COMPUTERS; Online Services; COMPUTERS; System Administration; Storage & Retrieval; Andre fag (naturvidenskab og teknik); Andre fag